Assemblies of the genomes of parasitic wasps using meta-assembly and scaffolding with genetic linkage. Issue 1 (9th November 2021) - Wittmeyer, Kameron T; Oppenheim, Sara J; Hopper, Keith R
Abstract: Safe, effective biological-control introductions against invasive pests depend on narrowly host-specific natural enemies with the ability to adapt to a changing environment. As part of a project on the genetic architectures of these traits, we assembled and annotated the genomes of two aphid parasitoids, Aphelinus atriplicis and Aphelinus certus . We report here several assemblies of A. atriplicis made with Illumina and PacBio data, which we combined into a meta-assembly. We scaffolded the meta-assembly with markers from a genetic map of hybrids between A. atriplicis and A. certus . We used this genetic-linkage scaffolded (GLS) assembly of A. atriplicis to scaffold a de novo assembly of A. certus . The de novo assemblies of A. atriplicis differed in contiguity, and the meta-assembly of these assemblies was more contiguous than the best de novo assembly. Scaffolding with genetic-linkage data allowed chromosomal-level assembly of the A. atriplicis genome and scaffolding a de novo assembly of A. certus with this GLS assembly, greatly increased the contiguity of the A. certus assembly to the point where it was also at the chromosomal-level. However, completeness of the A. atriplicis assembly, as measured by percent complete, single-copy BUSCO hymenopteran genes, varied little among de novo assemblies and was not increased by meta-assembly or genetic scaffolding. Furthermore, the greater contiguity of the meta-assembly and GLS assembly had little or no effect on the numbers of genes identified, the proportions with homologs or functional annotations. Increased contiguity of the A. certus assembly provided modest improvement in assembly completeness, as measured by percent complete, single-copy BUSCO hymenopteran genes. The total genic sequence increased, and while the number of genes declined, gene length increased, which together suggest greater accuracy of gene models. More contiguous assemblies provide uses other than gene annotation, for example, identifying the genes associated with quantitative trait loci and understanding of chromosomal rearrangements associated with speciation.